Quickscan Assesses Risk of Long-Term Sickness Absence: A Cross-Sectional Validation Study. Issue 2 (February 2019) - Goorts, Kaat; Vandenbroeck, Sofie; Vander Elst, Tinne; Rusu, Dorina; Du Bois, Marc; Godderis, Lode
Abstract : Objective: Increasing long-term sickness absence in many countries asks for specific measures regarding return-to work. Methods: The risk of long-term sickness absence was assessed using a questionnaire containing work-related, function-related, stressful life-events-related, and person-related factors. Additionally, workers' occupational health physician estimated the worker's chances for work resumption. Reliability, construct, and criterion validity of the questionnaire were measured. Results: Two hundred seventy-six patients and 35 physicians participated in the study. The reliability was satisfying ( α > 0.70) for all scales, except for perfectionism ( α = 0.62). The results of the CFAs showed that the hypothesized factor models fitted the data well. Criterion validity tests showed that eight predictors significantly related to the estimation of the occupational physicians ( ρ < 0.05). Conclusions: The scales of the questionnaire are reliable and valid, and may be implemented to assess sick-listed workers at risk who might benefit from a rehabilitation program.